Bacaan Ayat-Ayat Al-Qur’an pada Praktik Zikir Batu di Desa Tingkara, Kec. Malangke, Luwu Utara - Teguh Arafah Julianto; Kaharuddin; Muhammad Fahmi Kurniawan (AL-AQWAM: Jurnal Studi Al-Quran dan Tafsir, 2022)
This study aims to find out the Qur’an subsection in the process of stone zikir and its objectives in Tingkara Village. Thus, this research formulate the problem statements as follows: what is stone zikir?, What are the readings on the tradition of stone zikir in Tingkara Village?, and What is the purpose of carrying out the stone zikir in Tingkara Village?. The method used in this research is maudu‘i and descriptive-qualitative method with an interpretive and sociological approach. Data collection techniques conducted trough observation, interviews and documentations. The data analysis techniques, namely analysis by collecting data, data reduction, data display and drawing conclusions. The results of this study indicate that in essence the reading pronounced in the implementation of stone zikir is pure sourced from al-Qur’an’s subsection, namely QS al-Ikhlas/112 as the core and several other readings such as QS al-Fa>tih}ah/ 1, QS al-Falaq/113, QS al-Nas/114. The tahlil reading (la ilaha illa Allah). Stone zikir is conducted with the aim of praying together for people who have passed away and the recitation of surah al-Ikhla>s} on stones is done with the intention of presenting the reward to the people who have passed away.